Proceedings of the 14th ACM International Conference on Multimodal Interaction 2012
DOI: 10.1145/2388676.2388728
|View full text |Cite
|
Sign up to set email alerts
|

Measuring enjoyment of an interactive museum experience

Abstract: Museums are increasingly being equipped with interactive technology. The main goal of using technology is to improve the museum-going experience of visitors. In this paper, we present the results of a study with an electronic quest through a museum aimed at children in the age of 10-12. We wanted to find out whether personalization of the quest effects enjoyment. For this purpose we involved an interactive multi-touch table in the experiment, which also offered the opportunity to add the element of collaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…One of the key opportunities that locative media provides is the ability to traverse between the screen and physical spaces, creating hybrid and mediated experiences of place. These technologies are increasingly being implemented across heritage and cultural sites, like museums and monuments (van Dijk, Lingnau, & Kockelkorn, 2012), with varying degrees of success (Ciolfi, 2013). Technology, in particular, location-aware mobile applications, are playing an increasingly important role in shaping the visitor's experience of cultural and historical sites and locations.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key opportunities that locative media provides is the ability to traverse between the screen and physical spaces, creating hybrid and mediated experiences of place. These technologies are increasingly being implemented across heritage and cultural sites, like museums and monuments (van Dijk, Lingnau, & Kockelkorn, 2012), with varying degrees of success (Ciolfi, 2013). Technology, in particular, location-aware mobile applications, are playing an increasingly important role in shaping the visitor's experience of cultural and historical sites and locations.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the method called Fun Toolkit [6] is designed for children who require a reduced cognitive skill level, since to be able to respond, the child must fill in or select one of the options presented to them. Smileyometer [35] is a visual scale tool (VAS) based on the Likert scale with ratings from 1 to 5, where each level on the scale is represented by facial expres sions, i.e. a disappointed face corresponds to (1) and a very happy face to (5).…”
Section: Methods Advantages Disadvantages Directmentioning
confidence: 99%
“…We measured participants' experience of reading each text using the Intrinsic Motivation Inventory (IMI), a widely-used (Van Dijk, et al, 2012) and validated (McAuley, et al, 1989;Tsigilis and Theodosiou, 2003) instrument for measuring self-reported subjective experiences in experimental tasks.…”
Section: Confidence and Connectionmentioning
confidence: 99%